Peranan Front Office dan Admin Operasional dalam Menunjang Kualitas Pelayanan Jamaah di Tengah Kenaikan Fuel Surcharge Umrah - Mauludia Mugianto; Burhan Starfrezar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the role of front office and operational administration in supporting the quality of pilgrim service at an Umrah travel company amidst the increase in aviation fuel surcharges. The study used a qualitative approach using the Systematic Literature Review (SLR) method based on PRISMA guidelines, supported by observations and interviews during an internship at an Umrah travel company. Data sources were obtained from SINTA 5-accredited national journals, Google Scholar, field observations, interviews, and company documentation. The results indicate that the front office plays a crucial role in establishing communication, providing information, and addressing pilgrim needs and complaints. Meanwhile, operational administration plays a role in managing travel administration, such as visa processing, ticketing, departure schedules, and coordinating pilgrim operations. The study also shows that the increase in aviation fuel surcharges has resulted in increased operational costs and adjustments to Umrah package prices, requiring travel companies to implement service adaptation strategies and operational efficiency. Furthermore, the use of digital communication and strong coordination between company departments helps improve the effectiveness of pilgrim service. Thus, the quality of Umrah travel services is influenced by the ability of the front office and operational administration to provide professional, communicative, and organized service amidst the dynamics of the Umrah travel industry.